Analysis of Wireless Network Quality Using Quality of Service Method (Case Study: BAPEDA of South of Sumatera Province) - Misinem, .; Gerry Praja, Mukti (INTI International University, 2023)
Information technology networks are growing rapidly, especially in computer networks using wireless. Wireless computer networks support various human jobs communicating using the internet, such as uploading or downloading files. We need an exemplary wireless network in its services to carry out these activities. To find a condition of a wireless network functioning correctly, we need a method to measure it. The technique that can be used is Quality of Service (QoS). QoS is a method that uses several indicators to measure the quality of a wireless network. These indicators are bandwidth, delay, and packet loss. The results showed that the measurement of wireless networks in BAPEDA Province South of Sumatera shows good quality. The TYPHON version indicator indicates this, the delay value is below 150 ms, and the packet loss is 0%.